Why do first-time mothers not intend to breastfeed? --A qualitative exploratory study on the decision-making of non-initiation in Jingzhou, China - Yang Fei; Ze-Yu Zhang; Wen-Ning Fu; Li Wang; Jing Mao (BMC, 2022)
Abstract Background Although breastfeeding is one of the top priorities for public health in China, the rate of breastfeeding is still low and a large number of women do not initiate breastfeeding due to various reasons. Hence, this study aimed to understand the decision-making of non-initiation and reveal the underlying reasons in order to protect, support, and promote breastfeeding. Methods In-depth, exploratory interviews were carried out with 13 new mothers who did not initiate breastfeeding. The collected data were analyzed by inductive content analysis. Results Although mothers generally understood the protective effects of breastfeeding, they believed that formula milk is a good alternative to human milk and even better in some aspects. Five core themes related to non-initiation decision-making emerged: (1) expected breastfeeding stress; (2) maladjustment to the maternal role; (3) concerns about physiological issues; (4) the lack of knowledge about the risks of artificial feeding; (5) belief that it is better not to initiate than to interrupt. Conclusions The environment for mothers to breastfeed in China is not supportive enough, and the medical staff and families should be held responsible for the non-initiation of breastfeeding. More professionals are needed to support mothers to solve their problems and breastfeeding education should be further expanded.